A Multimodal Discourse Analysis of American Animated Feature Film "The Wizard of Oz" and Japanese Anime "Spirited Away" - ضبع، ناردين ماجد مكرم; يونس، نجوى إبراهيم عبدالفتاح; عابدين، عزة عبدالفتاح (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2021)
يحاول هذا البحث دراسة مساهمة تحليل الخطاب متعدد الوسائط في فيلم والت ديزني (The Wizard of Oz) وهايو ميازاكي (Spirited Away). يدرس المحتوى نموذج الوسائط المتعددة لكريس وفان لوفين. كما هو موضح في قراءة الصور: القواعد النحوية للتصميم المرئي (2006)، لمناقشة قواعد التصميم المرئي التي تفك رموز الأنماط المختلفة للتمثيل، وأنماط التفاعل، وكيف يمكن فك تشفير التجربة بصريا، وكل ذلك يساهم في معنى النصوص المرئية وكذلك الصور المتحركة. ضمن هذا الأساس المنطقي، تستكشف الدراسة الحالية نموذج تحليل الخطاب متعدد الوسائط لاستجواب كيفية رسم الصور المتحركة على أنماط الاتصال مثل موقف الكاميرا، الاتصال، والموقف، والمسافة، والألـوان، وتعبيرات الوجه والإيماءات جنبا إلى جنب مع الكلمات لجعل المعنى. The present paper attempts to examine the contribution of MD (Multimodal Discourse Analysis) of Walt Disney's The Wizard of Oz (1939) and Hayao Miyazaki's Spirited Away (2001). The investigation of the content is done using Kress and van Leeuwen's multimodality model (2006). As illustrated in Reading Images: The Grammar of Visual Design (2006), this paper intends to discuss the visual design grammar which decodes the different patterns of representation, patterns of interaction, how experience can be visually decoded, and all that contributes to the meaning of visual texts as well as moving images. Within this rationale, the present study explores the paradigm of Multimodal Discourse Analysis to interrogate how moving pictures draw on modes of communication such as camera attitude, posture, contact, distance, colors, facial expressions and gestures in combination with words to make meaning. Thereby, Multimodality is employed to show how fictional characters communicate and interact with each other not just through writing but also through speaking, gesture, gaze, and visual form
Keywords: الأفلام الكرتونية -- أفلام الرسوم المتحركة -- النصوص المرئية -- الصور المتحركة